Role of ESAT-6 in pathogenicity of Beijing and non-Beijing Mycobacterium tuberculosis isolates. (January 2022) - Mahghani, Ghorban Ali; Kargar, Mohammad; Ghaemi, Ezzat Allah; Kafilzadeh, Farshid; Davoodi, Homa
Abstract: Background: Mycobacterium tuberculosis Beijing genotype was associated with tuberculosis outbreaks and increased transmissibility. To understand the variation in virulence between Beijing and non-Beijing clinical isolates of M.tuberculosis genotypes, the esat- 6 gene sequencing, and its expression was compared in the macrophage environment. Materials & methods: Among 64 nonrepetitive, culture-positive M.tuberculosis, DNA extraction of 24 and 40 pure confirmed Beijing and non-Beijing isolates was accompanied by the boiling method. esat-6 gene PCR amplification and their sequencing were carried out by specific primers and its expression was performed on human macrophage cell line U937 after 6, 12, and 18 h of exposure to bacilli. The esat- 6 mRNA transcription and expression in M. tuberculosis treated macrophage by Real-Time PCR and Western blot method. Results: Data analysis based on sequencing of the east-6 gene PCR product showed that this gene exists in all isolates and there are no changes or single nucleotide variation between the Beijing and non-Beijing isolates. In Beijing strains, the esat-6 expression was increased during the study times, but it was constant in non-Beijing isolates. esat-6 gene expression in Beijing isolates reached to about 44.9 times more than non-Beijing isolates after 18 h incubation on the macrophages cell line. Conclusion: esat-6 is a conserved gene both in Beijing and non-Beijing isolates of M.tuberculosis . More expression of the east-6 gene in the macrophage model may indicate that this gene is likely to play a more important role in increasing the pathogenicity of Beijing strains. Highlights: Beijing lineage Mycobacterium tuberculosis has successfully disseminated worldwide. To clarify the difference in the pathogenicity of Beijing and non-Beijing genotypes of M.tuberculosis non-repitative positive culture isolates and relationship with the esat-6 gene in the U937 macrophage environment. Any differences in nucleotide sequence and expression of the esat-6 gene between two groups were evaluated three times (6, 12 and 18 h) after treatment. Our data showed that no SNP and a significant increase in esat-6 gene, in both transcriptional (Real-Time PCR) and translational (Western Blot) level, in Beijing strains, in contrast to non-Beijing isolates. It was time-dependent and the best time in dU937 cell line is 18 h after exposure of macrophage.